Double Decline Balance Method pada Aktiva Tetap Berwujud - Dina Satriani; Vina Vijaya Kusuma; Sefti Melinda (UNIVERSITAS RAHARJA, 2022)
Primkokas has assets used for daily operational activities. The asset has an economic lifespan of more than one year and is not for resale. In this case, the company will manage the asset into a long-term investment called fixed assets. Fixed assets require a management and special policy in calculating depreciation by using the double declining method. The result of this study is in calculating depreciation using the double declining balance method is done by multiplying the depreciation rate twice the accelerated depreciation rate from the initial book value each year. the amount of acquisition costs minus accumulated depreciation.